Combining Fast Imaging and Variable Temperature Studies in Atomic Force Microscopy. (28th May 2018) - Magonov, Sergei; Wu, Shijie
Abstract: Fast imaging in Atomic Force Microscopy enhances the capability of studying phase transitions and surface properties of materials at variable temperatures. This is demonstrated by measurements of several polymers [poly(diethylsiloxane), low-density polyethylene and ethylene-octene copolymer] and bitumen at low (down to -20°C) and high (up to +150°C) temperatures. Monitoring of structural transitions was performed at small and large (up to 40 μm) areas with 1-5°C/min cooling/heating rates. Novel data about dynamics and structural transitions of mesomorphic transitions and crystallization were obtained.